Supportive government policies, locus of control and student's entrepreneurial intensity: a study of India - Deepti Prakash; Shilpa Jain; Kavita Chauhan (Journal of Global Entrepreneurship Research, 2015)
The study surveyed 1255 (Male = 847, Female = 408) University students who are pursuing professional courses. The multivariate analysis of variance (MANOVA) was applied to identify the relationship between Gender, Locus of control (LOC) and whether students consider government long term policies as a support to start their own business with Entrepreneurial Intensity of Students. Entrepreneurial intensity captures the combined effect of degree (proactiveness, innovativeness and risk taking) and frequency (number of times entrepreneurial act is repeated) of entrepreneurship. It was found that type of locus of control (internal or external) differs significantly on Proactiveness, frequency of entrepreneurship, innovativeness and Entrepreneurial Intensity of students. It was also found that if students consider government long term policies as support to start their business; they differ significantly on Entrepreneurial Intensity (both degree and frequency of entrepreneurship).
Keywords: 650; Entrepreneurial intensity; locus of control; degree of entrepreneurship; frequency of entrepreneurship